Circulating tumor DNA, a new tool for diagnosing and monitoring cancer patients? - Bente Risberg (Bioingeniøren, 2016)
Background: Cell-free DNA (cfDNA) was first reported in 1948 at variable levels in blood samples, but more than two decades passed until it was discovered that it also could represent DNA from tumors. The amount cfDNA is often very low and in addition fragmented, which has made detection challenging. The revolution of methodology the last decades with regard to massive parallel sequencing (MPS) and digital PCR (dPCR) has increased the interest in detection of ctDNA.